Understanding floral variation in Leiothrix (Poales: Eriocaulaceae): anatomy, development and insights into pollination - Mascarenhas, Ana Angelica S. [UNESP]; Scatena, Vera L. [UNESP]; Oriani, Aline [UNESP] (Oxford Univ Press, 2022)
Leiothrix differs from other genera of Eriocaulaceae by having pistillate flowers with nectariferous and stigmatic branches that diverge at different heights on the style and staminate flowers with free or fused petals. To understand the ontogenetic processes that result in these morphological variations, we studied the development and floral vasculature in six species of the genus. In pistillate flowers, the nectariferous branches, which are in a carinal position, correspond to the apex of the carpels, whereas the stigmatic branches, in a commissural position, are formed by the marginal tissues of the carpels and initiate later than the nectariferous branches. The upper margins of the carpels elongate, forming a tubular structure that raises the stigmatic branches; the greater its development, the greater the distance between the stigmatic and nectariferous branches. In staminate flowers, the fusion of the petals appears to be post-genital in the median and apical portions and congenital in the more basal portion. Despite the differences in floral development, Leiothrix shares the same pattern of floral vasculature with other genera of Eriocaulaceae, exhibiting a central vascular plexus in the receptacle from which a single trace diverges for each sepal, petal and stamen. The staminodes are not vascularized. The dorsal carpellary bundles supply the nectariferous branches, but the ventral carpel bundles are reduced and are not involved in the supply of the ovules and stigmas. The differences in the height of insertion of the nectariferous branches are probably the result of selective pressure exerted by different groups of pollinating insects. Our hypothesis is that species in which the nectariferous branches are inserted below the stigmatic branches, and are therefore less accessible, exhibit a more specialized pollination system. The absence of nectariferous branches in L. angustifolia indicates secondary loss probably associated with spontaneous geitonogamy.
Keywords: flower; gynoecium; heterochrony; nectary; ontogeny; post; genital fusion